The relationship of spiritual intelligence factors and tendency to addiction and Its comparison between girls and boys students - Sara Afshar; Fariborz Seddighi Arfaei; Asghar Jafari; Hossein Mohammadi (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Addiction is a chronic disease characterized by individual, physiological and social dysfunction.  Spiritual Intelligence is the ability to experience Situations that allow individuals to achieve greater knowledge and understanding and providing Grounds in life the to achieve perfection and progress.Spiritual intelligence effects tendency to high-risk behaviors as addiction. Present study aimed to determine the relationship of spiritual intelligence factors and tendency to addiction on girls and boys students.  Materials and Methods: in this study, 100 students were selected among students of Kashan university using multiple cluster sampling. Methodology was correlation. Data were collected by questionnaires of spiritual intelligence and tendency to addiction and were analyzed using Pearson's correlation coefficient and multi variable regression.  Results: results indicated that there was significant relationship between the factors of understanding and communication with source and spiritual life with tendency to addiction (P<0/01). This relationship wasn't different between girls and boys students. In addition, results showed that understanding and communication with source and spiritual life can predict tendency to addiction) P<0/01(  Conclusion: The results provide some evidence that the factors of spiritual intelligence can predict part of changes of tendency to addiction. Therefore, in order to decrease the tendency of individuals to addiction suggested that their spiritual ability have been enhanced by doing cultural- educational packages.  Keywords: spiritual intelligence, communication with source, spiritual life, tendency to addiction For downloading the full-text of this article please click here.